RESPONSE OF THE PEOPLE OF BATUBARA REGENCY TO THE MUI BATUBARA FATWA ON THE PROHIBITION OF MARRIAGE BY WALI MUHAKKAM - Mirdiana Putri Ibsah; Sukiati; Imam Yazid (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2024)
In Indonesia regulations, namely the Compilation of Islamic Law (KHI) that are recognized as guardians, there are only two, namely the guardian of the nasab and the guardian of the judge and there is no mention of the guardian of the muhakkam. However, the reality is that in the community it is known that there is a marriage by the wali muhakkam in Batubara district. Wali muhakkam is a person appointed by both prospective husband and wife to act as guardian in the marriage contract. The legalization is because there is an opinion of jurisprudence scholars who allow marriage by the wali muhakkam. This is where there is a gap between the regulations of the Compilation of Islamic Law (KHI) and what happens in the coal community what should happen. From here, the problem arises that there are those who complain and demand rights in terms of the child's birth certificate and the inheritance rights that they should get, because from the beginning the bride and wife were not officially registered by the Marriage Registration Committee (PPN), so the problem became a dilemma for ordinary people who did not understand the pillars of marriage in Islam in its entirety. The purpose of this study is to find out the marriage by the muhakkam guardian  in Batubara district, as well as to find out the community's response to the MUI Batubara Fatwa regarding the prohibition of marriage by the muhakkam guardian. The research method used in this study uses the type of empirical or field juridical research and is descriptive analytical. In this case, the source of research information was obtained from the Muslim Community of Batubara district who carried out the appointment of muhakkam guardians. The results of this study show that the wali muhakkam is not valid as long as the wali nasab and wali hakim are still there.